Rheumatoid pneumoconiosis: A study in colliery populations in the East Midlands coalfield. Issue 6 (November 1967) - Lindars, David C.; Davies, Dewi
Abstract : The routine chest radiographs of more than 21, 000 miners from 23 unselected collieries in the East Midlands have been used for a study of rheumatoid pneumoconiosis and progressive massive fibrosis (P.M.F.). A broadened radiological concept of rheumatoid pneumoconiosis was used in diagnosis. The prevalence of simple pneumoconiosis categories 1, 2, and 3 was 5·5%, and of P.M.F. 0·59%. There were 55 cases accepted as rheumatoid pneumoconiosis, a prevalence of 0·26%. Thirty-two of these had positive latex fixation or Rose-Waaler tests for rheumatoid factor. The prevalence of P.M.F. was found to increase with increasing simple pneumoconiosis prevalence. A slight correlation between rheumatoid pneumoconiosis and simple pneumoconiosis prevalence was also found, but the bulk of the increase in P.M.F. was due to non-rheumatoid cases. The latter was closely paralleled in incidence by that of category 3 simple pneumoconiosis. Grouped results showed that rheumatoid pneumoconiosis occurred in between 2·3% and 6·2% of all men affected by pneumoconiosis. When examined on a geographical basis all areas exhibited a similar prevalence of rheumatoid cases, with the exception of Mansfield, where there was a significant excess. This excess was not significant when serologically positive cases only were considered. The findings are discussed in the light of the auto-immune theory for the development of massive lesions in the lungs of coal miners.